من أجل مُقاربة أسلوبيَّة مَعْرفية لنقد التَّرْجَمَة الأدبيَّة: تجسيد العلاقة بين الأنا والآخر في الترجمة الروائية أُنْمُوذَجًا. - شترات منير; فرڤاني جازية (Maalim, 2026)
The present study aims to show the importance of the cognitive stylistic approach, which is able to explore theories that relate linguistic choices to cognitive structures and processes. In fact, there has always been a strong tendency to view style – cognitively – as a reflection of mind and as closely tied up with the nature of literature both within and outside translation studies. In this regard, the cognitive stylistic view of context considers it as a cognitive entity, this cognitive view of context has affected approaches to the translation of style and the extent to which it is possible to achieve the same cognitive persuasion as in the original novelistic text, as well as the degree of the embodiment of the Same/Other dialectic. We also seek, through this paper, to search for the best translation strategy to transfer a struggling Algerian novel written in French, to Arabic; and if what we experience as a result of reading is a changed mental state, how do we ensure when translating that the reader of our translation also experiences a change in mental state? How can we prepare a cognitive stylistic model that enables the critic to evaluate this narrative text produced by translation in order to improve it?